2021
DOI: 10.3390/ijms222312934
|View full text |Cite
|
Sign up to set email alerts
|

The MAPK Signaling Pathway Presents Novel Molecular Targets for Therapeutic Intervention after Traumatic Spinal Cord Injury: A Comparative Cross-Species Transcriptional Analysis

Abstract: Despite the debilitating consequences following traumatic spinal cord injury (SCI), there is a lack of safe and effective therapeutics in the clinic. The species-specific responses to SCI present major challenges and opportunities for the clinical translation of biomolecular and pharmacological interventions. Recent transcriptional analyses in preclinical SCI studies have provided a snapshot of the local SCI-induced molecular responses in different animal models. However, the variation in the pathogenesis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…Ligand-receptor interactions involve WNT7A-FZD2/6/LRP5 and PDGFA-PDGFRB, whereby Glia/ERG- and OPC-derived WNT7A and PDGFA are received by FZD2/6/LRP5- and PDGFRB-expressing neurons. Highlighting the requirement for extracellular matrix (ECM) remodeling and signaling to enact a pro-regenerative response (Bradbury et al, 2002; Monaghan et al, 2007; Zavvarian et al, 2021), multiple cell types including Neurons A express Fibronectin 1 (FN1), which is predicted to direct strong interactions with SDC4-, ITGAV-, ITGA5- and ITGB1-expressing cells. Conversely, Glia/ERGs are a major source of outgoing SEMA6A signaling, received by PLXNA4-expressing neurons to regulate axon guidance (Carulli et al, 2021; Runker et al, 2008; Squair et al ., 2023; Syed et al, 2016; Yoshida, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Ligand-receptor interactions involve WNT7A-FZD2/6/LRP5 and PDGFA-PDGFRB, whereby Glia/ERG- and OPC-derived WNT7A and PDGFA are received by FZD2/6/LRP5- and PDGFRB-expressing neurons. Highlighting the requirement for extracellular matrix (ECM) remodeling and signaling to enact a pro-regenerative response (Bradbury et al, 2002; Monaghan et al, 2007; Zavvarian et al, 2021), multiple cell types including Neurons A express Fibronectin 1 (FN1), which is predicted to direct strong interactions with SDC4-, ITGAV-, ITGA5- and ITGB1-expressing cells. Conversely, Glia/ERGs are a major source of outgoing SEMA6A signaling, received by PLXNA4-expressing neurons to regulate axon guidance (Carulli et al, 2021; Runker et al, 2008; Squair et al ., 2023; Syed et al, 2016; Yoshida, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of the neuroplasticity and tissue repair following SCI are key to the functional recovery of SCI patients (18). However, the effects of current treatment for SCI are still limited in neural regeneration, and understanding the underlying mechanisms in the process of SCI provides opportunities for the targeted therapy of SCI (19,20). In this study, we identified 6 hub genes (Cd44, Timp1, Loxl1, Col6a1, Col3a1, Col5a1) and key biological mechanisms involved in the process of SCI based on bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The current clinically approved neuroprotective regimen, involving the administration of methylprednisolone sodium succinate (MPSS), is known to suppress the immune response through alteration of the MAPK network [ 65 , 66 , 67 , 68 ]. Interestingly, a recent comparative cross-species transcriptional analysis has highlighted the therapeutic potential of MAPK signaling in traumatic SCI [ 22 ]. The scarless healing process post-SCI seen in regenerative species, such as salamanders, may be explained by the downregulation of MAPK orthologs.…”
Section: Mapk Signaling Networkmentioning
confidence: 99%
“…The scarless healing process post-SCI seen in regenerative species, such as salamanders, may be explained by the downregulation of MAPK orthologs. Due to the observation that these genes are upregulated in mammals and downregulated in salamanders post-SCI, they may be worth investigating as potential therapeutic targets [ 22 ].…”
Section: Mapk Signaling Networkmentioning
confidence: 99%
See 1 more Smart Citation